2014
DOI: 10.1007/s00792-014-0676-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-active enzymes identified by metagenomic analysis of deep-sea sediment bacteria

Abstract: Subseafloor sediment samples derived from a sediment core of 60 m length were used to enrich psychrophilic aerobic bacteria on cellulose, xylan, chitin, and starch. A variety of species belonging to Alpha- and Gammaproteobacteria and to Flavobacteria were isolated from sediment depths between 12 and 42 mbsf. Metagenomic DNA purified from the pooled enrichments was sequenced and analyzed for phylogenetic composition and presence of genes encoding carbohydrate-active enzymes. More than 200 open reading frames co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In addition, there is growing interest in the role of marine microorganisms in biogeochemical processes, biotechnology, pollution and health. In recent years, many authors have focused on the great potential of marine microbes for use as prolific producers of bioactive substances, and they have exploited the vast marine microbial treasures for utilization as sources of drugs and antimicrobial agents [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. Extremophiles are organisms that are capable of living in particular ecosystems that are characterized by high (Thermophiles) or low temperatures (Psycrophiles), high ionic strength (Halophiles), acidic or alkaline pH values (Acidophiles, Alkalophiles), anaerobic conditions (Anaerobe), high pressures (Piezophiles), UV radiations and Polyextremophiles e.g., Thermoacidophiles and Thermohalophiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is growing interest in the role of marine microorganisms in biogeochemical processes, biotechnology, pollution and health. In recent years, many authors have focused on the great potential of marine microbes for use as prolific producers of bioactive substances, and they have exploited the vast marine microbial treasures for utilization as sources of drugs and antimicrobial agents [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. Extremophiles are organisms that are capable of living in particular ecosystems that are characterized by high (Thermophiles) or low temperatures (Psycrophiles), high ionic strength (Halophiles), acidic or alkaline pH values (Acidophiles, Alkalophiles), anaerobic conditions (Anaerobe), high pressures (Piezophiles), UV radiations and Polyextremophiles e.g., Thermoacidophiles and Thermohalophiles.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy for biomolecule stabilization in response to thermal stress is multifactorial, and it involves the investment of all the cellular components such as DNA, RNA, proteins, ribosomes, cell membranes, and biopolymers [2,8,9,10,11,12]. Particular attention has been concentrated on thermophilic microorganisms from marine hot springs and hydrothermal vents because of the marked ability of some of them to produce and secrete polymers and enzymes that are suitable for industrial purposes [12]. …”
Section: Introductionmentioning
confidence: 99%
“…65 Based on 14 C dating, sediment ages at drilling site C9006A in Suruga Bay were 5,155 («158) years before the present (BP) at 12 mbsf and 6,321 («548) years BP at 41 mbsf. 66 The calculated sedimentation rate based on the 14 C-dated sediment ages was 25,000 mm/1,000 years, which is much faster than any other sedimentation rates reported. Humic acid derived from plant fragments can be transported vertically by pore water in the sediment, which may partly contain foreign humic acid transported from the upper and lower horizons.…”
mentioning
confidence: 64%
“…Members of this family are abundant in marine and freshwater habitats and have been isolated from seawater [2, 3], sea ice [4], fresh water [5], glaciers [6, 7], marine plants and animals [4, 8]. In addition, metagenomic studies have shown the presence of Bacteroidetes in marine sediments [9, 10]. Members of the Flavobacteriaceae are also found in the human microbiota [11, 12], soil [13], insects [14], food and dairy products [15].…”
Section: Introductionmentioning
confidence: 99%